Differential circadian pattern of water and Na excretion rates in the metabolic syndrome. (August 2014) - Fezeu, Leopold; Bankir, Lise; Hansel, Boris; Guerrot, Dominique
<x xml:space="preserve">Abstract</x> This study comparatively investigated the chronobiology of water and Na excretion rates (W-ExcR and Na-ExcR) in 46 non-diabetic metabolic syndrome (MS) patients. The circadian pattern of W-ExcR was independently associated with the nocturnal dipping of systolic blood pressure (β = −3.1). During oral glucose tolerance test, the rise in plasma insulin (β = 34.0) and the insulinogenic index (β = 4.1) were independently associated with the day/night ratio of W-ExcR. The circadian pattern of Na-ExcR was not significantly associated with the latter variables. This study strongly suggests that the chronobiology of mechanisms involved in the regulation of water excretion may be more specifically altered in the MS.